Two features of dynamics of the charged particles in external magnetic field and in field of electromagnetic wave - Buts, V.A. (Вопросы атомной науки и техники, 2006)
It has shown that regimes with superdiffuse in space of velocity are inherent for moving of charged particles in external magnetic field and in fields of electromagnetic waves. The regimes with dynamic tunneling were finding too.